ANALISIS PENGUNGKAPAN MANAJEMEN RISIKO (BUKTI INDONESIA) - Hesti Hardana; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effectiveness of risk management disclosures where explicit disclosures are needed by users in assessing the material risks that exist in the company. This study also examines what factors influence the level of risk management disclosure. This study examined the top 130 companies (based on market capitalization ranking) listed on the IDX in 2016. The level of risk management disclosure was assessed using thematic content analysis methods, then tested with regression analysis to see which governance factors affected the level of risk management disclosure.The findings of this study indicate that the level of risk management disclosure provided is quite high. Factors that have a positive influence on the level of disclosure of risk management are institutional ownership (INSTOWN), and Beta shares (BETA). However, the proportion of Audit Committee expertise (ACEXPTS) shows a significant negative relationship. Whereas the proportion of Independent Commissioners on the Board of Commissioners (BINDP), the expertise of the Board of Commissioners (BEXPTS), the presence of the Risk Committee joined by the Audit Committee (RCAC) or not incorporated (RCSA), the presence of the Technology Committee (TC), involvement of Big 4 auditors (ADBIG4), market to book (MTB), leverage (LEV), and all control variables have no significant relationship to the level of risk management disclosures provided by the company.